2018
DOI: 10.1039/c8ra01781f
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of soybean dietary fiber and protein fortified rice grain by dry flour extrusion cooking: the physicochemical, pasting, taste, palatability, cooking and starch digestibility properties

Abstract: With the prevalence of chronic conditions in patients due to a dietary imbalance, the demand for inexpensive, nutritious and high dietary fiber extruded rice is increasing rapidly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Kumar and Prabhasankar () and Giuberti and Gallo () suggested that incorporation of legumes source in food products led to a significant reduction in rapidly digestible starch and increased the content of slowly digestible starch which is responsible for reducing the rate of starch hydrolysis, subsequently accountable for the low GI response. According to Liu et al (), decreased starch digestibility may be the combined effect of two phenomena; first one deals with the extrusion process which destroys the double helix structure of starch granules and subsequently increased the rapidly digestible starch (RDS). Another effect was consistent with the hypothesis that dietary fiber reduced the RDS content through embedment of RDS in their matrix, caused the formation of RS1, which can affect the digestion and absorption of starch.…”
Section: Resultsmentioning
confidence: 99%
“…Kumar and Prabhasankar () and Giuberti and Gallo () suggested that incorporation of legumes source in food products led to a significant reduction in rapidly digestible starch and increased the content of slowly digestible starch which is responsible for reducing the rate of starch hydrolysis, subsequently accountable for the low GI response. According to Liu et al (), decreased starch digestibility may be the combined effect of two phenomena; first one deals with the extrusion process which destroys the double helix structure of starch granules and subsequently increased the rapidly digestible starch (RDS). Another effect was consistent with the hypothesis that dietary fiber reduced the RDS content through embedment of RDS in their matrix, caused the formation of RS1, which can affect the digestion and absorption of starch.…”
Section: Resultsmentioning
confidence: 99%
“…Extrusion cooking could increase the phenolic content of rice bran or brown rice, which might be mainly due to the increase of these phenolics in free forms (Ti et al., 2015; Zhang et al., 2018). Additionally, the content of soluble dietary fiber (SDF) and TDF was also reported to be increased by extrusion cooking treatment (Liu et al., 2018). Therefore, the brown rice noodles prepared with extruded rice bran (BRN‐ERB) showed the highest contents of total phenolics, flavonoids, anthocyanin and dietary fiber.…”
Section: Resultsmentioning
confidence: 99%
“…This melting phenomenon marks the degree of gelatinization. Using these approaches, numerous efforts have been made to prepare extruded products (Paraman et al., 2012) and protein‐enriched rice (Liu et al., 2018). The attempts have been summarized in Table 1.…”
Section: Various Approaches To Rice Extrusionmentioning
confidence: 99%